Roseomonas Mucosa Bacteremia in an Immunocompetent Child - Sonu Kumari Agrawal; Bansidhar Tarai; Saloni Sehgal; Shalini Goldar (Indian Journal of Medical Specialities)
We report a case of bacteremia associated with Roseomonas mucosa isolated from an immunocompetent pediatric patient with no prior history of infection and bacteremia.